2018
DOI: 10.1136/thoraxjnl-2017-210728
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 mediates lung fibrosis, pulmonary vascular remodelling and hypertension in idiopathic pulmonary fibrosis: an experimental study

Abstract: JAK2 participates in PA remodelling and tension and may be an attractive target to treat IPF associated to PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 50 publications
3
68
0
Order By: Relevance
“…This is consistent with reports by others showing involvement of protein kinase C␤/ Erk1/2/NF-B signaling pathway in IL-17 induced myocardial fibrosis, both in vitro and in vivo (30), as well as the observation that suppression of NF-B by antisense oligonucleotides inhibits transdifferentiation of fibroblast toward myofibroblast in a bleomycin-induced pulmonary fibrosis mice model (68). Recent studies have also implicated a role for JAK2 and STAT3-dependent signaling in lung fibrosis (2,38,44,47,49,50) and ECM regulation (44,67). A recent study using IPF tissues revealed the presence of phosphorylated JAK2 and STAT3 in lung cells, suggesting a potential role of both JAK2 and STAT3 in the pathogenesis of IPF (39).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with reports by others showing involvement of protein kinase C␤/ Erk1/2/NF-B signaling pathway in IL-17 induced myocardial fibrosis, both in vitro and in vivo (30), as well as the observation that suppression of NF-B by antisense oligonucleotides inhibits transdifferentiation of fibroblast toward myofibroblast in a bleomycin-induced pulmonary fibrosis mice model (68). Recent studies have also implicated a role for JAK2 and STAT3-dependent signaling in lung fibrosis (2,38,44,47,49,50) and ECM regulation (44,67). A recent study using IPF tissues revealed the presence of phosphorylated JAK2 and STAT3 in lung cells, suggesting a potential role of both JAK2 and STAT3 in the pathogenesis of IPF (39).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, a recent study by Milara et al showed that lungs from patients with IPF expressed higher levels of STAT3 and JAK2, as well as phosphorylated STAT3 [32]. In another article they showed that this was also the case in pulmonary arteries in IPF [29]. As STAT3 possesses two phosphorylation sites that are known to be relevant to function: pSTAT3-Y705 and pSTAT3-S727 [37], it is important to distinguish between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-β (TGF-β) is another well discussed pathway in fibrosis development [19]. Recent publications [9,29,30], suggested Smad3 as a possible target of the IL-6 trans-signaling. Therefore, STRING analysis was performed, with the inclusion of the aforementioned targets, as well as Smad3.…”
Section: Phosphorylated and Total Smad3 Are Overexpressed In Ipf-hlfsmentioning
confidence: 99%
“…At present, lung diseases, including pulmonary hypertension, pulmonary fibrosis, chronic obstructive pulmonary disease, and even lung cancer, are a type of disease with extremely high mortality [1][2][3] . Although different diseases have different characteristics and pathogenesis, PASMC dysfunction plays an important role in the pathogenesis of various lung diseases [4][5][6] . Therefore, it is extremely important to further study the functions and regulation mechanisms of PASMCs, and the need to find new therapeutic targets is urgent.…”
Section: Introductionmentioning
confidence: 99%